(untitled) (Research, Society and Development, 2024)
The objective of the present study is to emphasize the importance of high-resolution computed tomography (HR-CT) in the early detection and characterization of lung adenocarcinomas, through a literature review study. The analysis details with HR-CT can identify lung nodules and differentiate between ground-glass opacities and solid nodules, which are crucial for determining prognosis and treatment options. In addition, it discusses the analysis of images (HR-CT) that offer valuable insights into the aggressiveness and invasiveness of tumors, highlighting the relevance of accurate diagnosis of in situ (AIS) and minimally invasive (MIA) adenocarcinomas, which have better survival rates. However, it is recognized that the differentiation between AIS, MIA, and invasive adenocarcinoma (IAD) is still challenging, requiring further studies to validate the accuracy of HR-CT in predicting tumor invasion. Finally, the discussion suggests that improvements in screening and imaging techniques may lead to more effective surgical interventions and better patient clinical outcomes.